THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK ENVIRONMENT, AND WORKLOAD ON TURNOVER INTENTION OF EMPLOYEES PT. BUMI JAYA TRANSINDO SEJAHTERA - Hendri Dunan; Fadila Rama Novita (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
This study examines the effects of organizational culture, workload, and work environment on employee turnover at PT. Bumi Jaya Transindo Sejahtera. Using a quantitative research approach, the study collected data from all 74 employees at the organization through a questionnaire. The sampling technique used was saturated sampling due to the small population size. The data was analyzed using multiple linear regression analysis. The results showed that Organizational Culture (X1) and Work Environment (X2) had no significant impact on turnover intention. However, Workload (X3) was found to have a significant influence on turnover intention. Overall, this research highlights the importance of Organizational Culture, Work Environment, and Workload in understanding turnover intention. These findings provide valuable insights for organizations looking to improve employee retention strategies. Future research can explore specific interventions and policies to effectively address organizational culture, work environment, and workload concerns and reduce turnover intentions.